Hereditary Calcium Pyrophosphate Crystal Deposition Disease Simulating Spondyloarthropathy: Case Report - Ebru Umay,; Alev Çevikol Demirel,; Aytül Çakcı, (Archives of Rheumatology, 2007)
Familial calcium pyrophosphate crystal deposition disease (CPPD); is a deposition disease characterized with deposition of calcium pyrophosphate in soft tissue, joint capsule and fibrous and hyaline cartilage that can be seen in more than one clinical appearance, inflammatory, degenerative and sometimes with destructive joint and vertebra invasion (neurological complications related to this can occur) and that can rarely lead to tophustumoural soft tissue calcifications. The disease has two forms; primary and secondary. A small part of primary form is hereditary and majority of it is idiopathic form. In the hereditary form, clinical initiation is generally poliarticular together with progression signs in the 3rd and 4th decades. There is a severe disease course, progression, deformity in joints and spoondyloarthropathy which rarely cause ankylosis in comparison to sporadic disease. Autosomal dominant inheritance has been demonstrated in studies performed in United Kingdom and United States of America. It is generally characterized with mutation in the short arm of the 5th chromosome (5p15.1 gene locus), or disorders in the pyrophosphate metabolism of the chondrocytes. ANKH gene codes the membrane protein responsible for the transmembranous transport of the synovial inorganic pyrophosphate in the chondrocytes. In the ANKH gene mutation, micro crystal forms appear in the extracellular matrix of the tendons and cartilages as a result of the increase of the extracellular inorganic pyrophosphate on a genetic basis. Sporadic form occurs with olygoarticular preference (knee and hand joints) in the 6th and 7th decade. Secondary form is associated with endocrine and metabolic diseases (hyperparathyroidism, hypothyroidism, hypomagnesemia, hypophosphatasia, hemochromatosis) trauma and surgical procedures. Here, we present a case followed up with the diagnosis of Ancylosing Spondylitis because of complaints regarding the spina and joints, and used various drugs, which was in fact a case of hereditary calcium pyrophosphate crystal deposition disease. (Rheumatism 2007; 22: 80-3)